Effects of Ethanol Blending on the Formation of Soot in n-Heptane/Air Coflow Diffusion Flame - Yuchen Ya; Xiaokang Nie; Licheng Peng; Longkai Xiang; Jialong Hu; Wenlong Dong; Huaqiang Chu (Journal of Chemistry)
Laminar diffusion flame was used to study the effect of ethanol on n-heptane flame in terms of the morphology and microstructure of soot under atomization combustion. For the same carbon mass flux at the outlet of the burner, the ratio of ethanol doping in n-heptane was changed, and the soot was collected from the axial positions of the flame at different heights using the thermophoresis probe method. The results showed that the flame height increased significantly with the increasing ratio of ethanol doping. When the ratio of ethanol and n-heptane (CE/CN) was 1.5, the flame height increased by 10 mm compared with that of pure n-heptane flame. Besides, the temperature in the center of the flame decreased with the increasing ratio of ethanol doping, but the temperature in the low position was higher than that in the pure n-heptane flame, and the temperature in the high position was lower than that in the pure n-heptane flame. However, the flame temperature was the highest when the proportion of ethanol in the mixture was greater than that of n-heptane. The temperature at the flame center decreased with the increasing ratio of ethanol doping, while the temperature at the flame edge increased with the ratio. The primary particle size of soot (soot size hereafter) in all working conditions increased with the increase of flame height, which was in line with the general growth law of soot. Moreover, the soot size at the same height decreased with the increasing ratio of ethanol doping, and this trend was most obvious at the flame height of 20 mm and 30 mm. Compared with pure n-heptane, when CE/CN was 1.5, the soot size at 20 mm and 30 mm decreased by an average of 34.83%, indicating that ethanol could inhibit the surface growth of soot particle. Furthermore, the density of soot particles collected by a single copper net decreased significantly, indicating that ethanol could reduce the production amount of soot.